Efficiency Analysis of Palm Kernel Oil as a Raw Material in Improving Supply Chain Performance: Case Study at PT XYZ - Sinaga, Fika Harini; Nurmalina, Rita; Rifin, Amzul (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2023)
This study aims to analyze the efficiency of raw materials supply and measure supply chain performance at PT XYZ. The method used to measure supply chain performance is SCOR. This research is limited to PKO raw material from suppliers and lauric acid products by PT XYZ. Results showed that the method of raw material procurement in PT XYZ was already efficient. The supply chain performance in PT XYZ was good yet only the POF matrix gives an unfavorable result compared to the brancmark from a similar company. Commonly in running operation of production, PT XYZ has several steps of supply chain that only involve suppliers, PT XYZ and direct to customer. The result showed from the measurement of matrix: level 1 is POF=88.36%, OFCT=44 days, and CTCCT=51 days. In level 2, PT XYZ conducted all activities in planning process (P1-P5), executing (S2, M1, M2, M3, D2, D3 and DR1) and enabling. On the mapping of level 2 obtained that the result of deliver process have the lowest performance and analysis in level 3 should be conducted to explain the deliver process in more detail.